Targeting metals rescues the phenotype in an animal model of tauopathy. Issue 9 (31st August 2018) - Sedjahtera, Amelia; Gunawan, Lydia; Bray, Lisa; Hung, Lin Wai; Parsons, Jack; Okamura, Nobuyuki; Villemagne, Victor L.; Yanai, Kazuhiko; Liu, Xiang M.; Chan, Jacky; Bush, Ashley I.; Finkelstein, David I.; et al.
Abstract : Targeting metals improves the behavioural, anatomical and biochemical phenotype present in a mouse model of tauopathy. Abstract : Tauopathies are characterized by the pathological accumulation of the microtubule associated protein tau within the brain. We demonstrate here that a copper/zinc chaperone (PBT2, Prana Biotechnology) has rapid and profound effects in the rTg(tauP301L )4510 mouse model of tauopathy. This was evidenced by significantly improved cognition, a preservation of neurons, a decrease in tau aggregates and a decrease in other forms of "pathological" tau (including phosphorylated tau and sarkosyl-insoluble tau). Our data demonstrate that one of the primary mechanisms of action ofPBT2 in this model may be driven by an interaction on the pathways responsible for the dephosphorylation of tau. Specifically, PBT2 increased protein levels of both the structural and catalytic subunits of protein phosphatase 2A (PP2A), decreased levels of the methyl esterase (PME1) that dampens PP2A activity, and increased levels of the prolyl isomerase (Pin1) that stimulates the dephosphorylation activity of PP2A. None of these effects were observed when the metal binding site ofPBT2 was blocked. This highlights the potential utility of targeting metal ions as a novel therapeutic strategy for diseases in which tau pathology is a feature, which includes conditions such as frontotemporal dementia and Alzheimer's disease.